ECONOMIC ASPECTS OF CONVERGENCE OF TECHNOLOGIES OF EXTRACTION OF METALS FROM THE DEADENED RESOURCES - Khasheva, Zarema; Golik, Vladimir; Kravchenko, Nikolay; Milovanov, Vladislav; Adamyan, Zhanna (Revista Inclusiones, 2019)
The revival of the Russian economy of the post-reform period provides the deep transformation of production of goods assuming activation of development of breakthrough technologies on the importance. Development of new such technologies in the conditions of a new type of production of goods assumes the solution of a problem of convergence of technologies which can be realized in packages of territorial industrial clusters of integration of production and other organizations within the uniform territory. Manufacturing enterprises, joint in a cluster, can hold a steady position in the conditions of volatile market conditions due to flexible cluster structure, synergetic effect, and other advantages. Hundreds of billion tons firm wastes which can be raw materials for production of products at the extraction of metals from them are stored in storages of tails of mining and metallurgical production. Results of theoretical and experimental justification of an opportunity and expediency of utilization of tails of processing of metal ores after extraction from them the remained metals on mechanochemical technology are presented.